Experimental Study on the Hydraulic Impact of Discrete Top Blockages in Gravity Sewers - Jinzhe Gong; Joshua Sim; Benny Zuse Rousso; Lloyd H. C. Chua; Michael Thomas (Engineering Proceedings)
The current study presents experimental results on how discrete top blockages alter the upstream flow depth in a gravity sewer. A full-scale experimental circular open-channel system (DN150, 30 m length) was constructed to simulate a gravity sewer. Discrete top blockages with various heights (80, 90, 100 mm) were tested with various flow rates and channel slopes. For various scenarios, the flow depths just upstream of the blockage were measured and analysed to reveal the impact of the blockages. The measured flow depths consistently exceeded those predicted by a reference formula from the literature, underscoring the difficulty in developing generalisable models.